2021
DOI: 10.4300/jgme-d-20-01167.1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Teaching Environment: 3-Year Follow-Up of a Resident-Led Residents-as-Teachers Program

Abstract: Background Previous faculty-driven residents-as-teachers (RAT) models have had limited efficacy and sustainability. Objective To evaluate the acceptability and effects of a resident-led RAT program on resident teaching. Methods In October 2016, obstetrics and gynecology (OB/GYN) residents at a large academic institution implemented a resident-led RAT program,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…While this is not surprising given the breadth of literature citing benefits of RaT experience, it does suggest that this experience provides many of the benefits already identified in other RaT opportunities and supports FoEM RaT as a viable option. 4,[8][9][10][11][12][13][14][15][17][18][19][45][46][47] FoEM resident instructors reported increased core knowledge, which echoes improved educational outcomes shown in other studies. 14,46,47,67 This finding that teaching facilitates learning is also consistent with adaptive expertise and the master adaptive learner model.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…While this is not surprising given the breadth of literature citing benefits of RaT experience, it does suggest that this experience provides many of the benefits already identified in other RaT opportunities and supports FoEM RaT as a viable option. 4,[8][9][10][11][12][13][14][15][17][18][19][45][46][47] FoEM resident instructors reported increased core knowledge, which echoes improved educational outcomes shown in other studies. 14,46,47,67 This finding that teaching facilitates learning is also consistent with adaptive expertise and the master adaptive learner model.…”
Section: Discussionmentioning
confidence: 78%
“…RaT improved their teaching skills, an essential component of RaT experiences. [10][11][12][13][14][17][18][19] In addition to the benefits to the resident teacher's knowledge and instructional skills, we found that FoEM…”
Section: Discussionmentioning
confidence: 90%
“…Overcoming the barriers to designing, developing, and implementing RaT programs into orthopedic residency programs is well worth the effort as RaT programs have consistently shown to increase residents' confidence in teaching 17,25 , increase residents' clinical knowledge 2,26 and medical learners have reported an increased perception that their residents were effective teachers 27 . That said, longer-lasting impacts were seen when interventions were longer than a one-off workshop and supported with frequent reinforcement 5,17,28 .…”
Section: Discussionmentioning
confidence: 99%
“…This program followed a resident-led resident-as-teacher model, which has previously been described as a successful educational strategy [ 11 ]. Such an approach allowed for minimal ongoing faculty involvement, improving the program's feasibility.…”
Section: Discussionmentioning
confidence: 99%